If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1 + -9y) + 4y = 5 (-1 * 2 + -9y * 2) + 4y = 5 (-2 + -18y) + 4y = 5 Combine like terms: -18y + 4y = -14y -2 + -14y = 5 Solving -2 + -14y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -14y = 5 + 2 Combine like terms: -2 + 2 = 0 0 + -14y = 5 + 2 -14y = 5 + 2 Combine like terms: 5 + 2 = 7 -14y = 7 Divide each side by '-14'. y = -0.5 Simplifying y = -0.5
| 18x^2-84x+98= | | 6(4x-7)=3(8x+8) | | 10n^2-4=506 | | 4+18r-2=9r+98-3r | | 159-4x=41x+14 | | 2x^3+5x^2-3x+5=0 | | 10-9x=23-16x | | x+(x-8)=60 | | 6y+4y=90 | | (8y-4y^2)+(3y-9y^2)= | | (0.5*x^2)-(1.5*x)=0.375 | | (0.5*x^2)-(1.5*x)-0.375=x | | q^2+2q=1 | | 2x^2-18x-8=0 | | 3x+30=10x-54 | | x^2-4.1x+2.2=0 | | (x^4)+(15x^2)-16=0 | | -7.5x=60.0 | | 3n-7=29 | | 0.7-10=0.5 | | 12t=-51 | | 9r=-36 | | x^2((x^2)+15)-16=0 | | -6(2b+3)+(13b-3)=0 | | 36c^2=4c | | 6x^2-16-20x=0 | | 36c^2=4v | | 2(3+6x)-4=50 | | 2.5q-1.2-2.1q=-0.6q-2.7 | | 6-3(3x-2)=-24 | | x+2=-35000 | | x^4+15x^2-16=-2 |